Multiplication of Indian Chir Pine Seedling by Cuttings in Nursery Beds - Joshi, N. K.; Dhiman, R. C. (Indian Forester, 1992)
Multiplication of Indian Chir pine (Pinus roxburghii Sargent) cuttings was studies in the nursery beds 5 percent IBA-talc with 10 percent sucrose, 5 percent capaf and 25 peccent perhydroxybenzoic acid (phenol) resulted in 57.13 percent rooting and 91 67 percent callusing of non-rooted cuttings compared to 7.14 percent rooting and 35.35 percent callusing in control. IBA at low concentrations (one percent) induced higher rooting when side shoots of seedlings were gridled at base and auxin powder formulation rubbed at gridled and finally covered with black tape. Cuttings planted around earthen backed water filled pots have further improved rooting both quantitatively and qualitatively. Many cuttings developed a strong main ront similar to tap root in seedlings.